Researcher Profile: An Interview with Virginia Solis Zuiker, Ph.D. - Virginia Solis Zuiker (Journal of Financial Therapy, 2016)
Virginia Solis Zuiker is an Associate Professor in the Department of Family Social Science at the University of Minnesota. She teaches courses on personal and family finance, family financial counseling, family resource management, economic perspectives of families, and family decision-making. Her scholarly research focus is in the area of economic well-being of families with particular interest in self-employment and family-owned businesses. Her research focuses on the Hispanic family life and she is the author of “Hispanic Self-Employment in the Southwest: Rising Above the Threshold of Poverty,” (Garland Publishing, 1997). She received her B.S. from the University of North Texas, an M.S. from Texas Tech University, and a Ph.D. from The Ohio State University. She served three years on the Board of Directors for the Association of Financial Counseling and Planning Education.
Keywords: researcher profile; financial therapy; family-owned businesses; economic well-being